Good Agricultural Practices (GAP 1) Programme and Its Implications on Cocoa Yield of Participants in Ondo State, Nigeria (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
The continuous fall in the output of cocoa in Nigeria in the past years has been a great concern to the Nigerian Government. Cocoa which is the majorexport crop in Nigeria is experiencing drop in the foreign exchange earnings accruing to the Nigerian Government from its exportation. It is therefore necessary to restore the relevance of cocoa export to the forefront. This necessitated the Federal Government to embark on phase 1 of a programme called Good Agricultural Practices (GAP 1) in which selected cocoa farmers were trained on best sanitation practices that will improve cocoa production. This research determined the effects of farm sanitation training on cocoa output and also determined the relevance of farm sanitation training in cocoa production. Using random sampling procedure; one hundred and ten (110) respondents were selected from the 140 farmers trained on cocoa farm sanitation under the GAP 1 programme of Federal Ministry of Agriculture in partnership with Ondo State Agricultural Development Programme (ODSADP). A well-structured questionnaire was used to gather information from the farmers. Data were analysed using descriptive and inferential statistics such as Chi-square, Pearson Product Moment Correlation and paired T-test. The results revealed that majority (64.5%) of the farmers were male and married (67.3%). The average age of the respondents was 56 years, 18.2% had completed primary school education. The study revealed that cocoa farmers were trained on removal of black pods, cankers, mistletoes, chupons, termites and weeds. The findings also revealed that there was a significant relationship (x2 = 13.220, P = 0.040